Model handlu wzajemnego krajów RWPG w latach siedemdziesiątych - Najlepszy, Eugeniusz; Karpiński, Józef (Wydział Prawa i Administracji UAM, 1987)
The main task of the article is the evaluation of spatial distribution of the intensity of mutual trade of the CMEA countries performed by means of selected standards of international trade intensity. The results of the statistical analysis served to build a relatively simple model of intensity and structure of mutual trade turnover within the CMEA which characterizes basic properties of trade of all the CMEA countries in the '70. In order to model those basic properties and the aim of mutual trade of the CMEA countries the method of graphic interpretation was applied. In effect, the empirical image of the system of streams of mutual trade was obtained. It resembles most the monocentric model of international trade. The central element of that system is the Soviet Union; the trade relations linking the USSR with the European CMEA countries are on the average six times more intensive than with other members of the CMEA. In effect, the Soviet Union absorbed more than 3/4 of mutual trade of the European CMEA countries what means that the trade with other member countries constituted only 1/3 of mutual trade in the analysed period. Besides, the results of the empirical analysis of mutual trade within the CMEA prove the existence of interdependence between the shaping of the level of trade intensity and the system of the structure of goods. According to that regularity, the intensity of trade within the CMEA is the function of the share of raw materials and fuels.
The model of mutual trade of the CMEA countries in the '70